Effects of clove oil concentrations on blood chemistry and stress-related gene expression in Siamese fighting fish (Betta splendens) during transportation - Sintuprom, Chanoknan; Nuchchanart, Wirawan; Dokkaew, Sahabhop; Aranyakanont, Chak; Ploypan, Raveewan; Shinn, Andrew P.; Wongwaradechkul, Ratchakorn; Dinh-Hung, Nguyen; Dong, Ha Thanh; Chatchaiphan, Satid (Frontiers in Veterinary Science, 2024)
Siamese fishing fish (Betta splendens) or betta are usually subjected to a special method of transportation for global trade, where they are individually conveyed in plastic bags containing just enough water to cover their bodies. This study aimed to investigate the effects of transportation on their stress response by measuring haematological values, stress hormone levels, glucose levels, and stressrelated gene expression. Betta fish (average body weight 1.91 ± 0.42 g; n = 30) were exposed to simulated transport in a water volume of 40 mL for 12, 24, and 48 hours. Baseline levels (pre-transport) were measured prior to the experiment. The control group was transported using water without adding clove oil. Two treatment groups were transported using water with the addition of 1 and 3 mg/L concentrations of clove oil, respectively. The results revealed that transportation can be a factor that affects water quality. The pH and dissolved oxygen levels were significantly lower than baseline, while nitrite and total ammonia concentrations significantly increased. Correlating to the stress responses, significantly increasing total red blood cell counts, plasma cortisol levels, and up-regulating the expression of stress-related genes, including HSP70, GR, MR, and HIF-1α. The addition of 1 mg/L clove oil was found to reduce stress during the transport simulation, as evidenced by a reduction in these stress parameters. Conversely, increasing the concentration of clove oil to 3 mg/L significantly increased plasma cortisol after 12 hours of simulated transport, and up-regulated GR, MR, and HIF-1α expression. This study revealed that the transport process can stimulates stress in betta fish but adding a concentration of 1 mg/L clove oil to the transport water could mitigate this stress response and promote animal welfare during their transportation.